Probability updating-based adaptive hybrid coding (Tongxin xuebao, 2008)
A probability updating mechanism was proposed for entropy coding. To achieve the best coding efficiency,probability updating based huffman code and structured code were jointly used,and the best context model was selected according as the correlation of adjacent syntax elements. Experiment results demonstrate that both of the coding effi-ciency and computational complexity of this probability updating-based adaptive hybrid coding （PUAHC） were between UVLC and CABAC.